Rotningsstimulerande effekt och kemisk analys av vattenbaserad extraktion av vedartade och örtartade skott av Salix smithiana Willd. - Nilsson, Åsa; Anderberg, Annelie (2007)
Cuttings of Lonicera xylosteum L. were treated with willow extract to study the response in rooting capacity. The extracts were prepared by mixing chopped pieces of Salix x smithiana Willd. with water in a warring blender. The investigation comprised 2 types of salix extracts based on differences and dynamics between twigs in winter dormancy and twigs with new shoots.